Spatial Analysis of the Existence and Distribution of Medicinal Plants in Ghimbo Pomuan Customary Forest, Kampar Regency, Riau Province - Hanifah Ikhsani; Emy Sadjati; Azwin Azwin (Journal of Global Sustainable Agriculture, 2023)
Medicinal plants are included in the Non-Timber Forest Products group, which has a variety of benefits, especially for human life and high economic value. Its existence is abundant in one of the customary forests in Riau Province, Ghimbo Pomuan Customary Forest. For the preservation and planning of medicinal plant management activities, it is necessary to analyze the spatial distribution of medicinal plants and determine the relationship between accessibility factors and the presence of medicinal plants. This research aims to analyzed the spatial distribution pattern of medicinal plants, map the distribution of medicinal plants, and determine the factors that affect spatial distribution based on accessibility factors. This research was conducted between March and November 2023. This study found that Ghimbo Pomuan customary forest has 24 species of plants with a total of 324 medicinal plants.The seven medicinal plants with the highest number are kacip fatimah (Labisia pothoina) 106 individuals, mempening (Lithocarpus spp) 50 individuals, matoa (Pometia pinnata) 34 individuals, pasak bumi (Eurycoma longifolia) 32 individuals, binahong (Andredera cordifolia) 30 individuals, keladi tikus (Typhonium flagelliforme) 19 individuals and bintangur (Clophyllum soulatri) 9 individuals. The spatial distribution pattern of medicinal plants is clustered with the nearest neighbor index NNI 0.58. The most influencing factor is the distance from the river, which is then followed by the distance from the road and the distance from the settlement. The farther from the river, the number of medicinal plants tends to increase, the closer the distance from roads and settlements, the number of medicinal plants increases.